Pengaruh Flash Sale, Voucher Gratis Ongkir dan Star Seller Terhadap Keputusan Pembelian Konsumen di Platform Shopee (Studi Kasus Konsumen Shopee di Kota Malang). - Muhammad Efendi; Nur Hidayati; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The development of e-commerce in Indonesia has driven increasingly fierce competition among digital platforms to attract consumer attention and interest. Shopee, as one of the largest e-commerce platforms, implements various promotional strategies, such as flash sales, free shipping vouchers, and the Star Seller label, to influence consumer purchasing decisions. Based on these conditions, this study aims to analyze the influence of flash sales, free shipping vouchers, and the Star Seller label on consumer purchasing decisions on the Shopee platform.This study used a quantitative approach with descriptive methods. Data were obtained by distributing questionnaires to 95 Shopee user respondents in Malang City, selected using a purposive sampling technique. The collected data were analyzed using multiple linear regression. The results show that flash sales, free shipping vouchers, and the Star Seller label simultaneously have a positive and significant influence on consumer purchasing decisions. These findings suggest that appropriate promotional strategies and consumer trust in sellers play a crucial role in driving online purchasing decisions. Keywords: Flash Sales, Free Shipping Vouchers, Star Seller, Purchasing Decisions, Shopee